2019
DOI: 10.1101/744664
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antibody-induced crosslinking and cholesterol-sensitive, anomalous diffusion of nicotinic acetylcholine receptors

Abstract: Short title: Antibody-acetylcholine receptor diffusion and myastheniaThe abbreviations used are: BTX, α-bungarotoxin; mAb, monoclonal antibody; nAChR, nicotinic acetylcholine receptor; CDx, methyl-β-cyclodextrin; CDx-Chol, cholesterol-methyl-β-cyclodextrin complex; MSD, mean-squared displacement; SPT, single-particle tracking. Abstract Synaptic strength depends on the number of cell-surface neurotransmitter receptors in dynamic equilibrium with intracellular pools. Dysregulation of this homeostatic balance occ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The great majority of the nAChR trajectories appear to conform to the two-state physical model (Figure 3). Previous work from our laboratory showed that free-diffusing individual nAChR trajectories were interrupted by confinement sojourns of a few hundred millisecond duration (Mosqueira et al, 2018;Mosqueira et al, 2020). Turning-angle analysis (Burov et al, 2013;Sadegh et al, 2017) and escape-time analysis (Weigel et al, 2011) led us to conclude that the hindrance to motion experienced by diffusing molecules in the confined state was due to physical impediments, and the steepness of the turning-angle curves indicated high density of these physical obstacles, in agreement with an obstructed diffusion case (Weigel et al, 2012;Burov et al, 2013) (reviewed in (Krapf, 2015)).…”
Section: The Two-state Model: Confined and Free-diffusion Portionsmentioning
confidence: 99%
See 4 more Smart Citations
“…The great majority of the nAChR trajectories appear to conform to the two-state physical model (Figure 3). Previous work from our laboratory showed that free-diffusing individual nAChR trajectories were interrupted by confinement sojourns of a few hundred millisecond duration (Mosqueira et al, 2018;Mosqueira et al, 2020). Turning-angle analysis (Burov et al, 2013;Sadegh et al, 2017) and escape-time analysis (Weigel et al, 2011) led us to conclude that the hindrance to motion experienced by diffusing molecules in the confined state was due to physical impediments, and the steepness of the turning-angle curves indicated high density of these physical obstacles, in agreement with an obstructed diffusion case (Weigel et al, 2012;Burov et al, 2013) (reviewed in (Krapf, 2015)).…”
Section: The Two-state Model: Confined and Free-diffusion Portionsmentioning
confidence: 99%
“…The STORM study confirmed the heterogeneity of diffusional regimes, from the predominant subdiffusive to the infrequent superdiffusive motion. STORM nanoscopy was subsequently applied to characterize the diffusion of the receptor tagged with the monoclonal antibody mAb35 (Mosqueira et al, 2020). The motional behavior of the nAChRs changed, albeit subtly, suggesting that multivalent antibody-induced crosslinking of the receptor contributes to temporarily hinder its Brownian displacement and confines it in nanoscale domains of ~34 nm radius.…”
Section: Heterogeneity Of Nachr Lateral Diffusionmentioning
confidence: 99%
See 3 more Smart Citations